Severe Erosive Esophagitis Secondary to Gastric Outlet Obstruction Related to Pseudomyxoma Peritonei. Issue 1 (8th January 2021) - Braun, David S.; Bushe, Bryce; Lytvak, Irina; Kedia, Prashant
ABSTRACT: Pseudomyxoma peritonei (PMP) is a rare clinical condition characterized by a mucin-producing tumor. PMP tumor cells migrate to abdominal and pelvic sites, eventually enveloping intra-abdominal organs and compressing the gastrointestinal tract. Patients with PMP are often asymptomatic in early stages of the disease, but in later stages develop symptoms including abdominal pain, acute abdomen, increased abdominal girth, vomiting, and bowel obstruction. Nonspecific symptoms combined with a relatively modest accuracy of imaging modalities frequently lead to delay in PMP diagnosis and treatment, thereby increasing morbidity. We present a case demonstrating severe erosive esophagitis as a result of PMP-associated gastric antrum compression.